Sorting Out the Details: A Q method Study Investigating Wheat Industry Professionals’ Soil Health Management Practices, Information Needs, and Communication Preferences - Maureen Victoria; Jean A Parrella; Holli Leggette; Morgan Orem; Jamie Foster; Haly Neely; Clark Neely (Journal of Applied Communications, 2025)
There is a need to rethink the traditional approach to conservation outreach, especially among wheat producers in Texas, where adoption of soil health management practices remain low. The study is the first to use Q methodology to identify common viewpoints of wheat industry professionals regarding their beliefs and behaviors related to soil health management practices. After developing the concourse and Q set using interview data and previous research, we collected data from N = 36 wheat industry professionals who attended various grower events. During analysis, we extracted seven factors that each had between one and four defining variables and a composite reliability between .80 and .94. Together, the seven factors, each of which represented a common viewpoint, accounted for 59% of the variance. We used distinguishing statements and factor arrays to describe the group of professionals representing each viewpoint—Conservation-Resistant Practitioners, Management-Selective Practitioners, Conservation-Oriented Practitioners, Technology-Motivated Practitioners, Soil Health-Conscious Practitioners, Extension Adverse Practitioners, and Information-Seeking Practitioners. Participants generally disliked aspects of the traditional outreach approach, including print media (i.e., radio, fact sheets), one-on-one conservation planning (i.e., seasonal calls and visits from Extension agents), and demonstrations (i.e., did not need visual evidence from on-farm demonstrations that soil health management practices work). We also identified distinct soil health management behaviors, information needs, and communication preferences of each group that can be used to inform targeted outreach that may increase adoption of soil health management practices.
Keywords: conservation outreach; extension; Q method; soil health management; wheat producers